Penerapan Instruksi di Tahap Hypothesis Testing Pada Discovery Learning untuk Meningkatkan Kemampuan Menemukan dan Menghubungkan Konsep - Berliyana Indrasari; Sri Widoretno; Sri Dwiastuti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The research aims to improve the ability of student’s discovering and relating concept through implementationof instruction in hypothesis testing of Discovery Learning model. The research is a Classroom Action Research(CAR) conducted in 2 cycles. Subjects of this research were 29 students of Senior High School in Karanganyar.The research consist of: planning, acting, observing and reflecting. Data collected through observation,interview, documentation and concept map test. The data validation used triangulation method. The obtaineddata were analyzed using qualitative-descriptive analysing technique that consist of data reduction, data displayand drawing inference. The result of the analysis the ability of student’s discovering and relating conceptshowed by score of concept map in the pre-cycle is range 5,67%-9,97%, the average of concept map in the precycleis7,7%and10studentsgethighscoreofconceptmapfromaverage.CycleIisrange8,02%-37,65%,theaverageofconceptmapinthecycleIis23,23%and19studentsgethighscoreofconceptmapfromaverage.CycleIIisrange8,08%-42,73%,theaverageofconceptmapinthecycleIIis27,56%and15studentsgethighscoreof concept map from average, the conclusion of implementation of instruction in hypothesis testing ofDiscovery Learning model improved the score of concept map from cycle I to cycle II.